The Slavic connexion : it's not typical Texas (2019)
An international chat show on the politics, history, current events, and peoples of the Slavic world, sponsored by The University of Texas at Austin's Center for Russian, East European, and Eurasian Studies and Clements Center for National Security. Whether you're a Slavophile, a foreign affairs junkie, or simply a curious mind, The Slavic Connexion offers insightful, accessible, and even fun discussions on the sprawling region in the context of our hyperconnected world.